Analisis Kritis Atas Adaptasi Dan Interaksi Filsafat Mesir Kuno Dengan Islam - Nofitayanti, Nofitayanti; Firdaus, Endis; Kosasih, Aceng (Tarikh : Journal of Islamic History and Civilization, 2025)
The purpose of this study is to analyze the adaptation and interaction of ancient Egyptian philosophy with Islam to regenerate the history of science. This research uses a qualitative approach and literature study method. Based on the results of the research, the development of philosophy in Egypt today is one of the important parts of a number of philosophical developments in the world of Islām. Through Egypt, philosophy spread to various parts of Islām because Egypt had opened very wide opportunities for scientific activities and gave freedom to anyone to study philosophy in particular and science in general. The development of Islamic philosophy in Egypt consists of two forms, the first is in the form of efforts to preserve the study of philosophy by reprinting all philosophical turats that have developed and the second is the development of philosophy carried out by holding seminars and discussions on various interesting topics. In addition, in Egypt there are institutions that concentrate on studying and analyzing various scientific issues, including philosophy.